Evasão escolar no ensino superior: um estudo de caso no Instituto de Ciências Exatas e da Terra - Campus do Araguaia - Universidade Federal de Mato Grosso - Silveira, Carlos Eduardo Lopes (2024)
Dropout rates in higher education have become a growing concern for institutional leaders. Understanding the reasons that have led students to abandon their undergraduate programs is essential to combat this issue and develop effective interventions. In this context, this study aimed to answer the following guiding question: What are the reasons for student dropout in undergraduate programs at the Institute of Exact and Earth Sciences, Araguaia University Campus, Federal University of Mato Grosso (ICET/CUA/UFMT)? To achieve this objective, a case study was conducted using exploratory and descriptive research methods with a qualitative approach to support the construction of the theoretical framework and applied research. The research participants were undergraduate program coordinators, the institute director, the undergraduate and extension manager, and dropout students, defined as those who discontinued or did not enroll in undergraduate programs at ICET/CUA/UFMT between 2017 and 2021. Content analysis and descriptive statistics were used to analyze the data. The research identified personal, institutional, and external factors contributing to student dropout. It also provided insights into the perspectives of program coordinators, the institute director, and the research and extension manager regarding the reasons for dropout. The findings revealed that dropout is caused by a variety of factors, including academic failure, difficulty balancing work and studies, and a mismatch between the student's chosen course and their interests. These findings highlight the need for effective public policies and dedicated efforts from academic communities to address these issues. Furthermore, the study indicates that the institution requires a more aligned approach to its actions and broader dissemination among its members.It is hoped that this study will contribute to the development of strategies to combat dropout and reduce dropout rates in undergraduate programs at UFMT.